2022
DOI: 10.3390/nu14163331
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 Repletion Improves Vascular Function, as Measured by Cardiorenal Biomarkers in a High-Risk African American Cohort

Abstract: Background: 25-hydroxy vitamin D (Vit D)-deficiency is common among patients with chronic kidney disease (CKD) and contributes to cardiovascular disease (CVD). African Americans (AAs) suffer disproportionately from CKD and CVD, and 80% of AAs are Vit D-deficient. The impact of Vit D repletion on cardio-renal biomarkers in AAs is unknown. We examined Vit D repletion on full-length osteopontin (flOPN), c-terminal fibroblast growth factor-23 (FGF-23), and plasminogen activator inhibitor-1 (PAI-1), which are impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…However, a large number of studies have shown increased OPN mRNA and OPN protein levels in several forms of CKD including DKD, LN, IgAN, tubulointerstitial nephritis, glomerulonephritis, acute ischemic renal injury, interstitial inflammation, fibrosis, and hydronephrosis [13,[64][65][66][67][68] (Table 2). These studies indicate a correlation between high levels of OPN expression, which can be quantified using commercially available sandwich enzyme-linked immunosorbent assays [69], with kidney function measured by proteinuria, reduced creatinine clearance, fibrosis, and macrophage and T-cell infiltration [13,64,65,70] (Figure 2). Subsequently, OPN was later reported to be a powerful predictor of CKD including incipient DN [66,71].…”
Section: Potential Of Osteopontin As a Biomarker In Chronic Kidney Di...mentioning
confidence: 93%
“…However, a large number of studies have shown increased OPN mRNA and OPN protein levels in several forms of CKD including DKD, LN, IgAN, tubulointerstitial nephritis, glomerulonephritis, acute ischemic renal injury, interstitial inflammation, fibrosis, and hydronephrosis [13,[64][65][66][67][68] (Table 2). These studies indicate a correlation between high levels of OPN expression, which can be quantified using commercially available sandwich enzyme-linked immunosorbent assays [69], with kidney function measured by proteinuria, reduced creatinine clearance, fibrosis, and macrophage and T-cell infiltration [13,64,65,70] (Figure 2). Subsequently, OPN was later reported to be a powerful predictor of CKD including incipient DN [66,71].…”
Section: Potential Of Osteopontin As a Biomarker In Chronic Kidney Di...mentioning
confidence: 93%